Characterization of the intestinal microbiota during Citrobacter rodentium infection in a mouse model of infection-triggered Parkinson's disease. Issue 1 (9th November 2020) - Cannon, Tyler; Sinha, Anshul; Trudeau, Louis-Eric; Maurice, Corinne F.; Gruenheid, Samantha
ABSTRACT: Parkinson's disease (PD) is a neurodegenerative disorder that has been shown to be influenced by the intestinal milieu. The gut microbiota is altered in PD patients, and murine studies have begun suggesting a causative role for the gut microbiota in progression of PD. We have previously shown that repeated infection with the intestinal murine pathogen Citrobacter rodentium resulted in the development of PD-like pathology in Pink1 −/- mice compared to wild-type littermates. This addendum aims to expand this work by characterizing the gut microbiota during C. rodentium infection in our Pink1 −/- PD model. We observed little disturbance to the fecal microbiota diversity both between infection timepoints and between Pink1 −/- and wild-type control littermates. However, the level of short-chain fatty acids appeared to be altered over the course of infection with butyric acid significantly increasing in Pink1 −/- mice and isobutyric acid increasing in wild-type mice.